How Latin America is finding path to economic prosperity again: A just transition as target - Günther Maihold (Stiftung Wissenschaft und Politik (SWP), 2023)
The traditional image of Latin America as a troubled region seems to continue even after the Covid-19 crisis, this time in the wake of the war in Ukraine and the sanctions imposed by the West. Inflationary pressures, budget deficits and the danger that broad sections of the population will slip into poverty are fuelling negative scenarios. There are initial indications that some countries are already experiencing payment difficulties. Demands from Latin American governments for debt relief or the renegotiation of foreign debt are being put on the agenda as part of a reorientation of the development model towards sustainability and climate protection criteria. This requires a far-reaching structural change, away from the traditional commodity-based economies and towards an environmentally and socially compatible development path. Germany and Europe must also shift course by contributing to the conservation of natural resources and not just to their exploitation.
Keywords: 320; Latin America; economic development model; sustainability; climate protection; Just Transition; inflationary pressures; budget deficits